Forever England Based on a Novel by C.S. Forester - Forde, Walter; Knowles, Bernhard; Mills, John; Balfour, Betty; MacKay, Barry (John Mills Centenary Collection II)
Convincing adaptation of a C.S. Forester’s best-selling naval adventure; featuring a notable performance from John Mills in his first leading role. Born after a brief affair between his mother (Betty Balfour) and a naval officer (Barry Mackay); Brown joins the Royal Navy during the First World War and becomes marooned on the remote Galapagos island of Resolution when the cruiser HMS Rutland he is serving on is sunk. There his heroism and marksmanship with a rifle single-handily keep the German battlecruiser SMS Zeithen delayed in port whilst carrying out much-needed repairs. Eventually a British warship, commanded by the father he never knew, reaches the island to sink the enemy ship. Brown becomes a hero, but at what cost? [www.britmovie.co.uk]